PERANCANGAN PERPUSTAKAAN UMUM KOTA GORONTALO DENGAN PENDEKATAN SMART BUILDING - Reza Rachmadyanti (Jurnal Teknik Sipil, Arsitek, Perencanaan Wilayah (J-TSIAP), 2022)
This research want to analize The design of the Gorontalo City Public Library using the Smart Building Approach is a building design process with the function of being an educational, informative, and recreational facility located on Jl.Achmad Nadjamudin, Kota Tengah District, Gorontalo City. The selection of Kota Tengah District as the location for this design was based on the function and designation of strategic areas in accordance with the designated functions of the area, one of which is the education area which is closely related to the provision of libraries, which have been regulated and stipulated in the Gorontalo City Spatial Planning. Based on the data obtained from the research results, the provision of library facilities is one of the important factors in advancing the world of education in Gorontalo City. Libraries provide a variety of information, reading, recreational and commercial areas whose use is more open to all people using the Smart Building approach. As the recommendation, it is need to use Smart Building as an approach to design with advances in science and technology, intended to create a library in Gorontalo City, with a Smart building appearance supported by modern technology applied to building elements, attractive, and provide convenience to users. It is displayed on building facades, landscapes, utility systems, security and telecommunications systems, structures and building materials. The library development is also a solution to improve the culture of reading and obtaining information.